Cardiac contractility modulation to enhance optimized medical therapy and improve cardiac remodeling in advanced heart failure: a case report - Feng, Lina; Su, Lina; Ren, Jingyi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundGuideline-directed medical therapy (GDMT) for heart failure (HF) with reduced ejection fraction (HFrEF) has been demonstrated to significantly reduce morbidity and mortality. However, many patients, especially those with advanced HFrEF, are unable to tolerate optimal GDMT due to hypotension. Cardiac contractility modulation (CCM) is a novel therapeutic approach that enhances myocardial contractility and reverses cardiac remodeling, thereby improving cardiac function and quality of life in patients with HFrEF. However, whether CCM can bridge the hemodynamic vulnerability phase to facilitate GDMT optimization and improve patient prognosis remains unclear.Case presentationA 56-year-old man with dilated cardiomyopathy and HFrEF (NYHA functional class III) had recurrent hospitalizations for HF over the past 4 years. Due to hypotension (systolic blood pressure ≤90 mmHg), the patient was unable to tolerate full-dose GDMT, with sacubitril-valsartan limited to 25 mg twice daily, metoprolol succinate to 23.75 mg once daily, and spironolactone to 20 mg once daily. After a comprehensive evaluation, a CCM device was implanted as the most effective and evidence-based option. Postoperatively, the patient's blood pressure gradually improved, allowing initiation of the four major therapeutic drug classes, which were uptitrated to the maximum tolerated doses. With regular follow-up for 12 months, the patient showed dramatic improvements in exercise capacity and quality of life. More surprisingly, there was significant improvement in cardiac structural and functional remodeling. Echocardiography revealed that left atrioventricular dimensions returned to normal, left ventricular ejection fraction (LVEF) increased from 15% to 48%, and left ventricular global longitudinal strain (GLS) improved from −3.3% to −16.2%. NT-proBNP levels also decreased from 6,553 pg/ml to within the normal range.ConclusionThis case suggests that CCM may serve as a promising strategy to address the issue of poor GDMT tolerance due to hypotension, thereby facilitating GDMT optimization and improving cardiac remodeling patients with HFrEF.